2005
DOI: 10.1002/bjs.4880
|View full text |Cite
|
Sign up to set email alerts
|

Critical appraisal of femorofemoral crossover grafts

Abstract: When obtaining informed consent, simply describing patency and limb salvage rates does not provide an accurate picture of the outcome of femorofemoral grafting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 18 publications
0
11
0
3
Order By: Relevance
“…Mingoli et al [10] reported the at 10 years primary and secondary patency rates were 48.1% and 63.2%, respectively, like our study. Consequently, the reports that included the 5-year results were much more common for FCB, which allows a more confident assessment of long-term patency [11,12]. …”
Section: Discussionmentioning
confidence: 99%
“…Mingoli et al [10] reported the at 10 years primary and secondary patency rates were 48.1% and 63.2%, respectively, like our study. Consequently, the reports that included the 5-year results were much more common for FCB, which allows a more confident assessment of long-term patency [11,12]. …”
Section: Discussionmentioning
confidence: 99%
“…Because it was planned that the patient would undergo cesarean delivery, we were concerned that anticoagulant therapy may increase the risk of complications. Even though compared with aortofemoral bypass surgery, the cumulative 5‐year patency rate of femorofemoral bypass is relatively low (approximately 90% and 75%, respectively), femorofemoral bypass surgery can be considered during pregnancy under regional anesthesia, which is an important advantage in high‐risk patients . In addition, anticoagulant therapy is not required.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the long-term results, primary graft patency rates were 76%, 63%, and 63% at 1 year, 3 years, and 5 years after surgery, respectively. Reported 5-year patency rates of crossover femoro-femoral bypass range from 60% to 74% [2-6]. And those of femoro-AK popliteal bypass with PTFE graft were from 39% to 68% [7-9].…”
Section: Discussionmentioning
confidence: 99%